Development and Preliminary Evaluation of IRD-1-2-3: An Animated Video to Inform Transplant Candidates About Increased Risk Donor Kidneys. Issue 2 (February 2020) - Kayler, Liise K.; Majumder, Monami; Dolph, Beth; Cobler-Lichter, Michael; Cadzow, Renee; Feeley, Thomas H.
Abstract : Background: Current educational interventions about increased risk donors (IRDs) are less effective in improving knowledge among African American (AA) kidney transplant candidates compared to other races. We aimed to develop an IRD educational animated video culturally responsive to AAs and conduct feasibility testing. Methods: Between May 1, 2018, and June 25, 2018, we iteratively refined a culturally targeted video for AAs with input from multiple stakeholders. We then conducted a one group pre-post study between June 28, 2018, and October 29, 2018, with 40 kidney transplant candidates to assess the feasibility and acceptability of the video to improve participant knowledge and obtain feedback about IRD understanding, self-efficacy, and willingness. A mixed population was chosen to obtain race-specific acceptability data and efficacy estimates to inform a larger study. Results: Three themes emerged and informed video development; misattribution of IRD to kidney quality, IRD terminology as a barrier to meaningful understanding, and variable reactions to a 1:1000 risk estimate. The study cohort was 50% AA. Median IRD knowledge increased from 5 to 7.5 ( P = 0.001) overall and from 5 to 7 ( P < 0.001) among AAs. The frequency of positive responses increased pre-post video for understanding of (23% vs 83%, P < 0.001), self-efficacy to decide about (38% vs 70%, P < 0.001), and willingness to accept IRD kidneys (25% vs 72%, P < 0.001). Over 90% of participants provided positive ratings on each of the 6 acceptability items. Conclusions: A culturally responsive IRD educational video was developed in collaboration with key stakeholders. Quantitative results indicate the video was acceptable and promising to impact IRD knowledge among AA and non-AA kidney transplant candidates. Abstract : Supplemental Digital Content is available in the text.